Identification of binding sites for C‐terminal pro‐gastrin‐releasing peptide (GRP)‐derived peptides in renal cell carcinoma: a potential target for future therapy. (26th January 2015) - Ischia, Joseph; Patel, Oneel; Sethi, Kapil; Nordlund, Marianne S.; Bolton, Damien; Shulkes, Arthur; Baldwin, Graham S.
<x xml:space="preserve">Abstract</x> Objective To determine the expression and biology of the neuroendocrine growth factor gastrin‐releasing peptide (GRP) and other proGRP‐derived peptides in renal cancer. Materials and Methods Receptor binding studies, enzyme‐linked immunosorbent assay (ELISA) and radioimmunoassay, were used to quantitate the presence of proGRP‐derived peptide receptors and their ligands in renal cancer cell lines and human renal cancers. Biological activity of proGRP peptides was confirmed with proliferation, migration, and extracellular‐signal‐regulated kinases 1 and 2 (ERK1/2) activation assays in vitro. In vivo, ACHN renal cancer xenografts were treated with proGRP‐derived peptides to assess tumour size and necrosis. hypoxia‐inducible factor 1α (HIF1α) and vascular endothelial growth factor (VEGF) expression were investigated with Western blotting and ELISA respectively, to determine the possible contribution of the proGRP peptides to tumour viability. Results In ACHN cells that expressed both proGRP‐ and GRP‐receptors, the expression of proGRP binding sites was 80‐fold greater than the GRP‐receptor (GRPR). C‐terminal proGRP‐derived peptides stimulated the activation of ERK1/2, but with a different time course to GRP, consistent with the suggestion that these peptides may have unique cellular functions. Both GRP and proGRP47–68 stimulated proliferation and migration of ACHN cells in vitro, but only GRP reduced the extent of tumour necrosis in ACHN xenografts. GRP, but not proGRP47–68, was able to induce HIF1α and VEGF expression in ACHN cells. This may account in part for the reduction in necrosis after GRP treatment. C‐terminal proGRP‐derived peptides were present in all three renal cancer cell lines and a panel of human renal cancers, but mature amidated GRP was absent. Conclusion C‐terminal proGRP peptides are more abundant in renal cancers and their cell lines than the more extensively studied amidated peptide, GRP. These results suggest that C‐terminal proGRP‐derived peptides may be a better target for novel renal cancer treatments.